摆动活齿减速器的多目标模糊优化设计 - 梁尚明; 徐礼钜 (Jixie chuandong)
The fuzzy optimization theory is used for the design of swing movable teeth drives in this paper. On the basis of detailed conside ration of various fuzzy factors, the mathematical model of multi objective fuzzy optimization design for swing movable teeth drives is set. The constraint conditions and design variables are presented, and a method for finding the solutions of the model is proposed. Finally, a numerical example is given for illustration.